A Literature Survey on Android Malware Detection Using Artificial Intelligence - Kiran Joshi (AG Volumes, 2022)
A fall in the cost of mobile devices like smartphones and tablets, along with an improvement in functionality as well as service availability, has increased the usage of these devices in the last few years. With its openness as well as free availability, Android OS has become a prominent player in the mobile device industry, and a target for hackers. A number of recent findings and trends in Android malware research have been surveyed in this paper. An overview of the analysis as well as detection process is provided by a discussion of static as well as dynamic malware analysis techniques, followed by an examination of the benefits of artificial intelligence techniques such as machine learning or deep learning for the detection of malware in various Android applications.